Nanoindentation behavior in T-carbon thin films: a molecular dynamics study - Zhou, Runhua (2025)
T-carbon is a new allotrope of carbon materials, and it displays high hardness and low density. Nevertheless, the hardening mechanisms of T-carbon thin films under nanoindentation remain elusive. This work utilizes molecular dynamics simulation to explore the hardening mechanisms of T-carbon thin films under nanoindentation with variations of loading velocities and temperatures. The results reveal that a loading velocity increase at a given temperature raises the nanoindentation force. The increase in nanoindentation force is due to graphitization, which is related to the fracture of tetrahedral structures in T-carbon thin films. However, increased graphitization caused by an increased temperature lowers the nanoindentation force at a given loading velocity. The increased graphitization is influenced by both the fractured tetrahedrons and the deformation of inter-tetrahedron bond angles. This is attributed to the loss of thermal stability and the lower density of T-carbon thin films as the temperature increases. These findings have significant implications for the design of nanodevices for specific application requirements.